2016
DOI: 10.1186/s13053-016-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Implications of using whole genome sequencing to test unselected populations for high risk breast cancer genes: a modelling study

Abstract: BackgroundThe decision to test for high risk breast cancer gene mutations is traditionally based on risk scores derived from age, family and personal cancer history. Next generation sequencing technologies such as whole genome sequencing (WGS) make wider population testing more feasible. In the UK’s 100,000 Genomes Project, mutations in 16 genes including BRCA1 and BRCA2 are to be actively sought regardless of clinical presentation. The implications of deploying this approach at scale for patients and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…However, stakeholders had concerns about data safety, secondary findings, data sharing, and other practical aspects [34][35][36][37]. Additionally, a modeling study demonstrated issues that hindered the utility of actively seeking secondary findings using WGS in patients potentially at risk for breast cancer [38]. To our knowledge, there were no full economic evaluations published.…”
Section: Wgs Introduction Initiatives Incorporating Htamentioning
confidence: 99%
“…However, stakeholders had concerns about data safety, secondary findings, data sharing, and other practical aspects [34][35][36][37]. Additionally, a modeling study demonstrated issues that hindered the utility of actively seeking secondary findings using WGS in patients potentially at risk for breast cancer [38]. To our knowledge, there were no full economic evaluations published.…”
Section: Wgs Introduction Initiatives Incorporating Htamentioning
confidence: 99%